A comparative study of reflex thresholds for pure tone, narrow band noise and wide band noise in normal hearers and sensori neural hearing loss cases - MA, Mythili (Journal of All India Institute of Speech and Hearing)
Middle ear muscle reflex was elicited using different acoustic s1 imuli such as pure tone, narrow band noise and wide band noise. The test was administered on 100 normal hearing subjects, and 15 subjects with moderate sensori-neural hearing loss